A multimodal study on the effect of sex on Alzheimer's disease clinical and biomarker changes in adults with Down syndrome. (31st December 2021) - Iulita, M. Florencia; Bejanin, Alexandre; Vilaplana, Eduard; Carmona‐Iragui, Maria; Benejam, Bessy; Videla, Laura; Barroeta, Isabel; Fernandez, Susana; Altuna, Miren; Pegueroles, Jordi; Montal, Victor; Valldeneu, Sílvia; et al.
Abstract: Background: The study of sex differences in Alzheimer's disease (AD) is gaining increasing attention. Yet, few studies have examined the effect of sex in genetically determined forms of AD. Here, we explored the impact of sex on AD‐related clinical and biomarker changes in a population‐based cohort of adults with Down syndrome, who have a lifetime risk of over 90% to develop AD. Method: This is a cross‐sectional study of 549 adults with Down syndrome. We compared AD prevalence, as well as cognitive and AD biomarker changes, in relation to age and sex in the whole cohort. Participants underwent neuropsychological examination with the Cambridge Cognitive Examination for Older Adults with Down Syndrome (CAMCOG‐DS) and modified cued recall test (mCRT). Most also had at least one biomarker assessment of amyloid pathology (CSF Aβ42, Aβ42/40 ratio and amyloid‐PET), tau (CSF and plasma p‐Tau‐181) and neurodegeneration (CSF and plasma NfL, FDG‐PET and 3T structural MRI). We used within‐group locally estimated scatterplot smoothing (LOESS) models to compare the trajectory of biomarker changes with age in women versus men, as well as the interaction with the APOE ε4 allele. Result: The prevalence of AD across five‐year age intervals and the mean age at AD diagnosis was similar between men and women. Men and women had similar trajectories in CAMCOG scores with age, but men showed lower mCRT scores from age 45 years. There were no differences between men and women in the CSF Aβ42/40 ratio or amyloid‐PET, or in the trajectories of tau and neurodegeneration biomarkers. When considering the APOE genotype, women carrying the ε4 allele showed an earlier age at AD diagnosis and higher prevalence of symptomatic AD between ages 40‐45 compared to non‐carriers. The female advantage on mCRT scores was lost in women carrying an ε4 allele. Conclusion: Sex did not have a main effect on AD risk or biomarker changes. However, APOE ε4 modified the age at symptomatic AD diagnosis and age‐related mCRT scores in women, but not in men. These results emphasize the complexity of the relationship between biological sex and AD, and the need to further explore interactions with APOE ε4.